Oxford illustrated encyclopedia: Vol.7 - Peoples and Cultures (New York, 1993)
The book describes comprehensively each and every one of the many hundreds and thousands of peoples, tribes, nations, and societies in th world. It illustrates different aspects of human cultural and social organization by including exaples of certain regions, of certain "exemplary" peoples who are famous through particular anthropological studies and interpretation, and of political minorities, peoples whose antagonistic relationships with the larger states in which they live have brought them wide attention
Keywords: encyclopedias and dictionaries